Kepatuhan Wajib Pajak Dan Pemutihan Pajak Terhadap Penerimaan Pajak Kendaraan Bermotor Pada Samsat Padang Pariaman - Rasul Hamidi; Muhammad Rivandi (Jurnal Mutiara Ilmu Akuntansi, 2023)
The purpose of this study was to obtain empirical evidence of the influence, taxpayer compliance and tax bleaching on motor vehicle tax revenues. The location of this study is at the SAMSAT Padang Pariaman Office. The receipt of motor vehicle taxis all income or gains generated from motor vehicle taxes such as annual PKB, receipts from fines given to taxpayers who have arrears, as well as other vehicle tax revenues related to motor vehicle tax. The sample determination method used in this study is an incidental sampling method. The data collection method in this study is a questionnaire method that is distributed to motor vehicle taxpayers as many as 100 questionnaires. The data analysis technique used in this study is multiple linear regression analysis. Based on the results of multiple linear regression analysis, it shows that taxpayer compliance and tax bleaching have a significant positive effect on motor vehicle tax revenues. This research is expected to provide more in-depth information and understanding, and it is hoped that taxpayer compliance will increase and tax bleaching programs will continue to be held so that motor vehicle tax revenues increase.